Uterine artery Doppler and sFlt‐1/PlGF ratio: usefulness in diagnosis of pre‐eclampsia. (11th April 2013) - Gómez‐Arriaga, P. I.; Herraiz, I.; López‐Jiménez, E. A.; Gómez‐Montes, E.; Denk, B.; Galindo, A.
<x xml:space="preserve">Abstract</x> Linked Comment: Ultrasound Obstet Gynecol 2013:41:489–490